Achieving 11.95% efficient Cu2ZnSnSe4 solar cells fabricated by sputtering a Cu–Zn–Sn–Se quaternary compound target with a selenization process. Issue 16 (2nd April 2019) - Li, Xinchen; Zhuang, Daming; Zhang, Ning; Zhao, Ming; Yu, Xinping; Liu, Peng; Wei, Yaowei; Ren, Guoan
Abstract : CZTSe solar cells with 11.95% peak efficiency have been achieved by sputtering a quaternary compound target using the selenization process. Abstract : In this study, earth-abundant thin film Cu2 ZnSnSe4 (CZTSe) solar cells were fabricated by the magnetron sputtering of a quaternary compound target. Precursor films were deposited in a designed chemical composition followed by a selenization process under the mixed atmosphere of an active gas, H2 Se, and a carrier gas, Ar. Due to the existence of the Se element within the film, a relatively low concentration of H2 Se was utilized to mainly crystallize the precursors and also supplement Se. To explore the selenization process, the as-deposited CZTSe absorbers were annealed at different temperatures. The results of X-ray diffraction (XRD) and Raman scattering spectroscopy measurements showed that the CZTSe grains continuously grew after selenization. In this study, when the absorbers were annealed at 575 °C, the CZTSe solar cells were obtained with the highest efficiency of 11.95%, with the open circuit voltage ( V OC ) of 432.22 mV, short circuit current density ( J SC ) of 36.28 mA cm −2 and fill factor (FF) of 76.21%. The photoluminescence (PL) spectrum indicates that the peak center underwent a red-shift from the band gap ( E g ) of 90 meV. The analyses of fluctuation modules indicate that the electrostatic potential fluctuation is dominant for the band tail. The investigations demonstrate that sputtering of the Cu–Zn–Sn–Se quaternary compound target via the selenization process can be an effective and simple method for the fabrication of high-performance CZTSe solar cells.